THE ORIGINALITY IMAGE OF THAILAND’S CULTURE AFFECTING ON QUALITY AND VALUE PERCEPTION BASED ON THAI SENIOR TOURIST - Pharatt Run; Surachai Traiwannakij; Marlon Rael Astillero; Ada Marie Mascarinas; Guiyu Su (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The research aimed to study the causal relationship between the originality image of Thailand's culture, quality perception, and value perception based on Thai Senior Tourists. The questionnaires were constructed as a research tool for collecting data from 787 samples of Thai Senior Tourists who visited Thai cultural tourism. The data were analyzed by using second-order confirmatory factor analysis. The research findings indicated that the confirmatory factor model of the original image of Thailand's culture affecting quality and value perception based on Thai Senior Tourists had validity, and the developed causal relationship model was confirmed with the empirical data (Chi-square = 21.013, df = 19, P = 0.336, CMIN/DF = 1.106, GFI =0.994, AGFI=0.986, NFI= 0.995, IFI= 0.999, CFI=0.999, RMSEA =0.012) and the developed causal relationship model between the originality image of Thailand's culture, quality perception, and value perception based on Thai Senior Tourists had predicting ability at a reasonable and acceptable level at 64.8 % with its acceptance more than 40% Keywords: Originality image of Thailand's culture; Perception of quality; Perception of value